Identification of Photoperiod-Induced LncRNAs and mRNAs in Pituitary Pars Tuberalis of Sheep - Xia, Qing; Chu, Mingxing; He, Xiaoyun; Liu, Qiuyue; Zhang, Xiaosheng; Zhang, Jinlong; Guo, Xiaofei; Di, Ran (Frontiers in Veterinary Science, 2021)
The pituitary pars tuberalis (PT) is the regulating center of seasonal reproduction, which can sense the melatonin signal and eventually cause downstream changes of GnRH secretion through TSHβ. Recently, lncRNAs have been identified in animal reproductive tissues and they play important roles in reproductive regulation. Therefore, in this study, we expect to identify photoperiod-induced lncRNAs and genes in pituitary PT of sheep by comparison of expression profiles between short-photoperiod (SP) and long-photoperiod (LP). Through RNA-Seq, a total of 55472 lncRNAs were identified in pituitary PT of Sunite ewes. The number of diﬀerentially expressed (DE) genes and lncRNAs between SP and LP increased gradually with the extension of LP (from LP7 to LP42). The notable LP-induced candidate genes included EYA3, TSHB, SIX1, DCT, VMO1, AREG, SUV39H2, EZH2, and SP-induced genes involved ENSOARG00000012585, CHGA, FOS, SOCS3 and TH. In enriched pathways for DE genes and lncRNAs target genes between SP and LP, the reproduction and circadian related pathways were highlighted. In addition, the interactome analysis of lncRNAs and their targets implied that MSTRG.209166 and its trans-target TSHB, MSTRG.288068 and its cis-target SIX1, and ENSOARG00000026131 and its cis-target TH might participate in regulation of seasonal reproduction. Together, these results will help to determine important photoperiod-induced lncRNAs and genes and give us some new insights regarding the epigenetic regulation of seasonal reproduction in sheep.